2021
DOI: 10.34312/jgej.v2i1.9642
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Tingkat Kesejahteraan Masyarakat Nelayan Di Desa Lero Kecamatan Sindue Kabupaten Donggala

Abstract: The objectives of this research are: (1) to find out the Welfare Level of the Fishermen according to the World Bank (2) to find out the Welfare Level of the Lero Village Fishermen based on the Central Bureau of Statistics. Data were collected using observation, questionnaires, interviews, and documentation. Data analysis used in measuring fishermen's welfare using the income approach and BPS criteria. The results of the research show that (1) Based on the net income of fishermen for a month is IDR. 839.413, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The results of the study found that the net income of fishing households in Lero Village, Donggala Regency for a month was Rp. 839,413 which means less than the World Bank standard so fishermen in the village are categorized as poor or not yet prosperous (Mulviana;Laapo, 2021). For Jenilu Village itself, the average monthly income of fishing communities is Rp.…”
Section: Characteristics Of Fishermen's Activities and Income Levelsmentioning
confidence: 99%
“…The results of the study found that the net income of fishing households in Lero Village, Donggala Regency for a month was Rp. 839,413 which means less than the World Bank standard so fishermen in the village are categorized as poor or not yet prosperous (Mulviana;Laapo, 2021). For Jenilu Village itself, the average monthly income of fishing communities is Rp.…”
Section: Characteristics Of Fishermen's Activities and Income Levelsmentioning
confidence: 99%
“…The criteria for community welfare according to the Central Statistics Agency (BPS) are income, consumption, quality of residence, health, ease of education, and ease of transportation and information technology facilities. (M. Amin & Laapo, 2021), (In Law Number 11 of 2009 "Concerning Social Welfare" social welfare is a condition for the material, spiritual and social fulfillment of citizens in carrying out their social functions. (Nurhasanah et al, 2019), (Wijayanti & Darsana, 2015).…”
mentioning
confidence: 99%